2013
DOI: 10.1242/jeb.083147
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to an endotoxin challenge involves multiple immune parameters and is consistent among the annual-cycle stages of a free-living temperate zone bird

Abstract: SUMMARYTrade-offs between immune function and other physiological and behavioural processes are central in ecoimmunology, but one important problem is how to distinguish a reallocation of resources away from the immune system from a reallocation or redistribution within the immune system. While variation in baseline values of individual immune parameters is well established, studies in wild animals on multiple parameters during an immune response are lacking. It also remains to be tested whether and how immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 68 publications
5
77
1
Order By: Relevance
“…Thus, we found little support for a parasite-mediated change in immune functions and oxidative status. These results contrast with other studies on wild species, which showed significant sex-dependent change in immunological and oxidative state over the year (Pap et al 2010c;van de Crommenacker et al 2011;Hegemann et al 2012bHegemann et al , 2013Horrocks et al 2012;Rubolini et al 2012). However, most of these studies did not measure change in parasite pressure over the year (but see Horrocks et al 2012), making it difficult to pinpoint a direct association between variation in physiological state and parasite infection.…”
Section: Introductioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Thus, we found little support for a parasite-mediated change in immune functions and oxidative status. These results contrast with other studies on wild species, which showed significant sex-dependent change in immunological and oxidative state over the year (Pap et al 2010c;van de Crommenacker et al 2011;Hegemann et al 2012bHegemann et al , 2013Horrocks et al 2012;Rubolini et al 2012). However, most of these studies did not measure change in parasite pressure over the year (but see Horrocks et al 2012), making it difficult to pinpoint a direct association between variation in physiological state and parasite infection.…”
Section: Introductioncontrasting
confidence: 79%
“…Several studies have shown that components of the immune system may vary over the year; however, divergent changes were found between species, populations, and physiological traits, with no clear pattern of high and low responses in particular seasons (Møller et al 2003;Buehler et al 2008aBuehler et al , 2012Martin et al 2008;Pap et al 2010bPap et al , 2014Hegemann et al 2012aHegemann et al , 2012bHegemann et al , 2013Horrocks et al 2012). Sex differences in reproductive physiology or parental investment may also affect immune function, the defense capacity of the antioxidant system, and/or the oxidative damage (Alonso-Alvarez et al 2007; Metcalfe and Alonso-Alvarez 2013;Rubolini et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This was expected because natural antibodies are known to be more genetically determined than other immune parameters (Versteegh et al 2014) and do not change during immune challenges (Hegemann et al 2013a). Likewise as predicted, total immunoglobulin levels in circulation, a marker of the constitutive part of acquired immune function that reflects more long-term investment in immune function, was unrelated to stopover duration.…”
Section: Discussionmentioning
confidence: 99%
“…Given that natural antibodies have relatively low developmental, maintenance and use costs (Lee, 2006), are not sensitive as other immune parameters to changes in infection status (Matson et al, 2005), and fluctuate less across the annual cycle in red knots (Buehler et al, 2008) and in free-living red crossbills (Schultz, 2015), it is not surprising that natural antibodies did not respond to LPS injections in the present study. Additionally, despite the fact that increases in haptoglobin activity have been shown in other bird species Hegemann et al, 2013), haptoglobin is only one acute-phase protein that can increase in response to LPSinduced inflammation. Other positive acute-phase proteins such as C-reactive protein (CRP) can activate complement (reviewed in Gruys et al, 2005;Owen-Ashley and Wingfield, 2007), which is involved in mediating hemolysis and E. coli (ATCC 8739) killing ability (Matson et al, 2005;Millet et al, 2007).…”
Section: Lps Effects On Innate Immunitymentioning
confidence: 98%